Efectos diferenciales de la alabanza verbal, retroalimentación de los resultados sobre el mantenimiento de la tasa de respuesta aritmética - García, Cirilo H.; Almaguer, Virginia; Sánchez, Rosa M.; Martínez, María G.; Lambretón, Guillermo R.; Lambretón, Salvador (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
The effect of a combination of verbal praise and feedback of results, and the separate effects of praise and feedback on the maintenance of arithmetic response rate, previously obtained b y a combination of token economy, verbal praise and feedback of results, was studied. The subjects were five elementary school children classified by their teachers as slow learners.